Socioeconomic Factors and Health Status Disparities Associated with Difficulty in ADLs and IADLs among Long-Lived Populations in Brazil: A Cross-Sectional Study - Júlia Cristina Leite Nóbrega MSc; Juliana Barbosa Medeiros MSc; Tácila Thamires de Melo Santos MSc; Saionara Açucena Vieira Alves MSc; Javanna Lacerda Gomes da Silva Freitas MSc; Jaíza M.M. Silva MSc; Raisa Fernandes Mariz Simões MSc; Allisson de Lima Brito MSc; Mathias Weller PhD; Jair Lício de Ferreira Santos PhD; Tarciana Nobre Menezes PhD; Yeda Aparecida de Oliveira Duarte PhD; et al. (SAGE Publishing, 2021)
Objective: To evaluate the association between socioeconomic factors, health status, and Functional Capacity (FC) in the oldest senior citizens in a metropolis and a poor rural region of Brazil. Method: Cross-sectional study of 417 seniors aged ≥80 years, data collected through Brazil's Health, Well-being and Aging survey. FC assessed by self-reporting of difficulties in Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs). Chi-square tests and multiple logistic regression analyses were performed using "R" statistical software. Results: Socioeconomic and demographic inequalities in Brazil can influence FC in seniors aged 80 years and older. Comparatively, urban long-lived people had a higher prevalence of difficulties for ADLs and rural ones showed more difficulties for IADLs. Among urban oldest seniors, female gender and lower-income were correlated with difficulties for IADLs. Among rural oldest seniors, female gender, stroke, joint disease, and inadequate weight independently were correlated with difficulties for ADLs, while the number of chronic diseases was associated with difficulties for IADLs. Conclusion: Financial constraints may favor the development of functional limitations among older seniors in large urban centers. In poor rural areas, inadequate nutritional status and chronic diseases may increase their susceptibility to functional decline.